Validity Test of Cardiovascular Endurance Test Instruments Based on Aerobic Step Test - Maisyarah Sianipar; Liliana Puspa Sari; Alan Alfiansyah Putra Karo Karo (Journal Of Sport Education (JOPE), 2024)
Cardiovascular endurance is a fundamental component of physical fitness that significantly influences both health and physical performance. In physical education, assessing cardiovascular endurance is essential to monitor students’ fitness levels. However, laboratory-based tests such as the graded exercise test (GXT) are often impractical due to the need for specialized equipment and high costs. Therefore, there is a need for a simpler, more efficient, yet valid alternative instrument one of which is the aerobic step test. This study employed a quantitative approach with a criterion validity design. The research subjects consisted of 30 Physical Education students selected through purposive sampling. The primary instrument was the aerobic step test, in which recovery heart rate (HR1rec) was measured, while the comparative instrument was the graded exercise test (GXT) for VO₂max assessment. Data were analyzed using Pearson’s correlation test, simple linear regression, and Bland Altman agreement analysis with the assistance of SPSS software. The findings revealed a strong correlation between VO₂max derived from the aerobic step test and that obtained from GXT (r = 0.812; p < 0.001). The coefficient of determination indicated that the step test could explain 65.9% of the variance in VO₂max (R² = 0.659). Bland Altman analysis demonstrated a bias of –0.77 ml·kg⁻¹·min⁻¹ with limits of agreement of ±4.85, which is considered practically acceptable for field application. The aerobic step test is validated as a simple, practical, and efficient tool for assessing cardiovascular endurance among students. This instrument can serve as a reliable alternative to laboratory-based fitness testing in physical education settings where laboratory facilities are unavailable.